EFEKTIVITAS PENGGUNAAN KARTU KREDIT PEMERINTAH DAERAH SEBAGAI ALAT PEMBAYARAN PELAKSANAAN APBD PADA PEMERINTAH KOTA TANGERANG - Ni Made Sri Wardani; Maulida Salmi Utie; Faris Windiarti (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Payment using cards has been proven to be more effective and secure than cash payments. The implementation of cards used in payment transactions within the government is the Regional Government Credit Card (KKPD). With good cash management through KKPD, the Regional Government can minimize the use of cash reserves and reduce the risk of idle cash. The purpose of this study is to analyze the effectiveness of the implementation of the KKPD use policy in the Tangerang City Government and analyze the reasons why the implementation of KKPD in the Tangerang City Government has not been able to run optimally. This research is a qualitative descriptive study. The data sources used by researchers in this study are primary and secondary data. Data collection techniques in this study are semi-structured interviews, observation and documentation. The results of the study indicate that the use of KKPD Cash Reserves in the Tangerang City Government is still ineffective because there is still a lot of idle cash reserves. The implementation of the Regional Government Credit Card policy in Tangerang City is still only minimally implemented by existing SKPDs due to several obstacles.